2012
DOI: 10.1002/j.0022-0337.2013.77.4.tb05488.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Incidents, Successes, and Challenges of Community‐Based Dental Education

Abstract: In 2006, the Arizona School of Dentistry & Oral Health at A.T. Still University (ATSU ASDOH) implemented an intensive community-based education program for its inaugural fourth-year students called the Integrated Community Service Partnerships (ICSP) program. As part of the ICSP program, students spend half of their clinical experience (approximately ninety-ive days) in rotations at four or ive community-based clinics. More than sixty clinics in Arizona and throughout the country serve as rotation sites. ATSU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…In addition, they are gaining knowledge and appreciation for alternative career paths. The data also suggest these experiences have a positive impact on their understanding of the ethical and social issues related to oral healthcare . Evidence has shown that community‐based dental experiences have resulted in dental students’ perceived competence in multiple competency domains .…”
Section: Discussionmentioning
confidence: 82%
“…In addition, they are gaining knowledge and appreciation for alternative career paths. The data also suggest these experiences have a positive impact on their understanding of the ethical and social issues related to oral healthcare . Evidence has shown that community‐based dental experiences have resulted in dental students’ perceived competence in multiple competency domains .…”
Section: Discussionmentioning
confidence: 82%
“…In three studies, community rotations for fourth‐year students that ranged from 40 to 95 days were assessed 29 , 31 , 36 . In one of those studies, the effects of a six‐week non‐dental community‐based rotation for students prior to beginning their first year of dental school was examined 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Generally, outcomes assessed were affect, cognition, 29 , 35 personal and professional growth, 25 cultural competence and respect for diversity, 6 , 28 , 32 , 34 recognition of care disparities and social determinants of health, 28 lack of care access, 32 improving curriculum and identifying student difficulty, 36 and developing community leadership capacity 30 . Five studies focused on developing a sense of social responsibility, 6 , 26 , 27 , 31 , 32 and one focused on a “charity” versus “social justice” philosophical approach to care 27 .…”
Section: Resultsmentioning
confidence: 99%
“…An instructional strategy that emerged from Boud et al's theory is the Critical Incident Technique (CIT), a qualitative exercise in which the learner “describes an occurrence, the cause, and outcome. It is aimed at isolating vital components of an incident, identifying and evaluating key factors to yield a deeper understanding of the whole, and reassessing an assumption to bring forth change.” 9 As a pedagogy, CBL with reflection and CIT teaches students to bring their ideas to consciousness and begin to evaluate and make choices about what they believe, ethically and professionally, assisting in their personal and professional development 2, 5 7, 9,11, 13 15 . Education that develops cultural competence, values that reflect societal responsibility, and a desire to provide care to underserved populations is essential to creating a society that addresses oral health disparities 2 6 .…”
mentioning
confidence: 99%
“…Education that develops cultural competence, values that reflect societal responsibility, and a desire to provide care to underserved populations is essential to creating a society that addresses oral health disparities 2 6 . However, understanding if oral health students are internalizing an appropriate vision of their role as oral health professionals in the context of community is a question often raised 2, 6,9,10, 13 15 …”
mentioning
confidence: 99%